Geographical Factors in Diagnostic Delay among Multidrug Resistant Tuberculosis Patients - Nunuy Nuraeni; Hendarsyah Suryadinata; Bony Wiem Lestari (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Diagnostic delay is a factor that can increase the high burden of multi-drug resistant tuberculosis (MDR-TB). Xpert Mycobacterium tuberculosis/Rifampicin known as Xpert is a rapid diagnostic test to detect MDR-TB. Diagnostic delay defined the duration between a positive result of Acid Fast Bacilli (AFB) smear and positive result of MDR-TB by Xpert examination. This study aimed to compare the analysis of the geographical factors in the diagnostic delay of MDR-TB patients at Dr. Hasan Sadikin General Hospital as the top referral hospital in West Java Indonesia.Methods: This study was conducted in the period July−December 2016 using cross sectional design. A total of 152 MDR-TB patient data were collected from medical records of MDR-TB patients registered in MDR-TB clinic at Dr. Hasan Sadikin General Hospital in the period 2015−2016. The socio-demographic characteristics were collected and analyzed descriptively The diagnostic delay among MDR-TB patients was analyzed by Mann Whitney test.Results: Diagnostic delay of MDR-TB patients was 15 days in median, with a minimal and maximal delay of 2−140 days. There was a significant difference of diagnostic delay between patients from Bandung with a median of 9(2-135) days and patients from outside of Bandung with a median of 18(2-140) days, with p<0.01.Conclusions: MDR-TB patients from outside Bandung have a longer diagnostic delay than patient from Bandung . A further expansion of using Xpert as a rapid diagnostic test for MDR-TB patient is needed.